Kaempferol Promotes Vasorelaxation via KV2.1 Channel Modulation in the Coronary Arteries of Sheep - Bhati, Ajay; Gaur, Ashok; Sharma, Pratishtha; Sharma, Puneet; Purva, Kirti; Singh, Devendra; Kant, Lakshmi; Gaur, Shivangi; Pandey, Amit Kumar (Planta Medica)
Kaempferol, a flavonol found in various edible and medicinal plants possesses antioxidant, anti-inflammatory, and cardioprotective properties. The vasorelaxant effects of kaempferol were assessed using isolated coronary artery rings pre-contracted with potassium chloride (30 mM). Kaempferol induced a concentration-dependent relaxation in both endothelium-intact and endothelium-denuded coronary artery rings pre-contracted with potassium chloride (30 mM), indicating that its vasorelaxant effect is primarily endothelium-independent. Inhibition of nitric oxide synthase (NOS) with L-NAME (100 μM) and cyclooxygenase (COX) with indomethacin (10 µM) did not significantly alter the relaxation response, suggesting that nitric oxide (NO) and prostaglandins play a minimal role. The BKCa channel blocker TEA (1 mM), ATP-sensitive potassium (KATP) channel blocker glibenclamide (10 µM), and inward-rectifier potassium (KIR) channel blocker BaCl2 (30 μM) did not significantly affect kaempferol-induced relaxation. However, inhibition with the voltage-gated potassium (KV) channel blocker 4-aminopyridine (3 mM) significantly reduced the relaxation response indicating the involvement of KV channels. Furthermore, molecular analysis using RT-PCR confirmed the presence of the KV2.1 (KCNB1) gene in sheep coronary arteries, suggesting its role in kaempferol-mediated vasorelaxation. These findings suggest that kaempferol promotes vasorelaxation through an endothelium-independent mechanism, with partial involvement of KV2.1 channel. This study supports kaempferol’s therapeutic potential in cardiovascular disease, recommending its dietary inclusion as a strategy to lower the risk of cardiovascular diseases.